1993
DOI: 10.1007/bf00542334
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-associated proteins (SP-A, SP-B) are increased proportionally to alveolar phospholipids in sheep silicosis

Abstract: In silicosis, a profile of surfactant overproduction associated with type II epithelial cell hypertrophy and hyperplasia has been documented. In addition, enhanced accumulation of surfactant-associated protein A (SP-A) has been seen in the rat model of acute silicosis by 2 independent groups, but the exact role of these surfactant changes in silicosis are incompletely understood. In this study we measured in lung lavage surfactant total phospholipids and surfactant-associated proteins A and B (SP-A, SP-B). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Some investigators have postulated that increased levels of SP-A are associated with increased susceptibility to TB. This hypothesis is based on studies which showed that there were increased SP-A levels in subjects with silicosis, pulmonary alveolar proteinosis, and HIV, three diseases in which there is increased susceptibility to mycobacterial infection (8,16,35,36). Recent data have extended these observations, and polymorphisms in the SP-A gene are associated with susceptibility to TB in certain populations (9).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some investigators have postulated that increased levels of SP-A are associated with increased susceptibility to TB. This hypothesis is based on studies which showed that there were increased SP-A levels in subjects with silicosis, pulmonary alveolar proteinosis, and HIV, three diseases in which there is increased susceptibility to mycobacterial infection (8,16,35,36). Recent data have extended these observations, and polymorphisms in the SP-A gene are associated with susceptibility to TB in certain populations (9).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, patients with three diseases in which there is increased susceptibility to pulmonary mycobacterial infections, HIV, silicosis, and alveolar proteinosis, all have increased levels of SP-A in the bronchoalveolar lavage (BAL) fluid (BALF) (8,16,35,36). However, there is little data on the status of SP-A levels in patients with TB and how these levels change in response to therapy.…”
mentioning
confidence: 98%
“…Another pulmonary disorder associated with elevated levels of SP-A is silicosis (70), a condition associated with a lifelong predisposition to tuberculosis (71). The mechanisms for the elevation of SP-A in silicosis are unclear, but this may represent a compensatory mechanism by the lung to facilitate clearance of silica particles from the lower respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were removed by centrifugation at 6,300 g for 10 min, and aliquots were stored at Ϫ 20 Њ C until analysis. SP-B was measured by ELISA as previously described (27). SP-A was measured using ELISA rabbit anti-mouse SP-A antiserum.…”
Section: Construction Of the Sp-c-gm-csf Chimeric Genementioning
confidence: 99%